Gambaran Waktu Tunggu Pelayanan Resep di Puskesmas Mamburungan Kota Tarakan - Nur Syafika Safitri; Sari Wijayanti; Irma Novrianti (Politeknik Kaltara, 2024)
Waiting time is one of the factors affecting the satisfaction of patients who fill prescriptions at the health center. Long waiting times are a problem that often occurs in several health care facilities which can cause patient dissatisfaction. This study aims to see the average time required related to prescription services for non-recombinant and concocted drugs at the Mamburungan Health Center, Tarakan city. Descriptive research with quantitative is the type used in this study. The sampling technique used in this study was purposive sampling. Data was obtained using observation sheets with a total sample of 94 prescriptions from 47 non-recipe and 47 concoctions. Waiting time is declared optimal and ideal if the service provided for non-reciprocated drugs takes ≤30 and ≤60 minutes for concocted drugs. Meanwhile, according to the minimum service standardization at the Mamburungan Health Center, the ideal length of time for non-recipe prescriptions is ≤5 minutes while ≤30 minutes for concoction drugs. The data results from the study show that the average waiting time for prescription services for non-reciprocated drugs is 5 minutes while concocted drugs are 10 minutes. Based on the above results, it can be concluded that the prescription service time at the Mamburungan Health Center is by the specified standards, namely the Kepmenkes in 2008, and according to the standards of minimum services at the Mamburungan Health Center.